The Effect of Dividend Announcements on Stock Return Volatility - Romli, Annisa Aliffia; Nofal, Nofal; Husnah, Husnah; Anisah, Anisah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to examine the effect of dividend announcements on stock return volatility in companies included in the LQ45 index on the Indonesia Stock Exchange, particularly during the post-COVID-19 pandemic recovery period. Dividend information is regarded as an important signal for investors and can trigger market reactions that impact stock price fluctuations. The method used is an event study with the Wilcoxon Signed-Rank test to measure differences in stock return variance before and after dividend announcements over 5-day and 15-day periods. The results show a statistically significant increase in volatility during the 5-day period following the announcement (p = 0.043), but no significant change during the 15-day period. These findings indicate that dividend announcements trigger short-term reactions but do not have a lasting impact. This reflects that the Indonesian market is not yet fully efficient, and the price adjustment process to dividend information is still occurring gradually.